VISUAL COMFORT AND USER PERCEPTION CLASSROOM LECTURES IN BUILDINGS EDUCATION (International Conference on Social and Islamic Studies, 2021)
Visual perception or human response to visual conditions that are accessed by their visual senses, is strongly influenced by light because light is what allows us to access visual information. For that, it is important for us to be able to meet the need for light appropriately and in accordance with the needs of a space, both indoor and outdoor. Visual quality in the lecture classroom can have positive and negative impacts depending on the user and the factors that shape the visual quality in the lecture room. The purpose of this study was to measure and evaluate the visual comfort of natural lighting in classrooms that are directly related to the building envelope and to assess the perception of space users. Research Methods with a combination of qualitative and quantitative methods by distributing data from questionnaires and measurements in the form of tables, diagrams and graphs. The sample location of the study is an educational building in Makassar City. Data analysis was carried out using the comparative method by comparing the results of the questionnaire and measuring light intensity with correlation statistics and Likert scale. The results show that the forming factors of visual quality such as not using artificial light because it has an impact on shadows and heat in the room, the use of projector (LCD) media in the teaching and learning process, the atmosphere/impression of the visual quality of natural light, and the area and spatial arrangement are the dominant factors in providing comfortable perception for space users. Then the results of the measurement of light intensity show the average level ofroom illumination intensity of 300 lux. This is in accordance with the comfortable perception of the use of space in the classroom and the SNI standard for lecture rooms of 250 lux.